Gazing at horror: body performance in the wake of mass social trauma - Tang, Cheong Wai Acty (Rhodes University, Faculty of Humanities, Department of Drama, 2006)
This thesis explores various dilemmas in making theatre performances in the context of social disruption, trauma and death. Diverse discourses are drawn in to consider issues of body, subjectivity and spectatorship, refracted through the writer's experiences of and discontent with making theatre. Written in a fractal-like structure, rather than a linear progression, this thesis unsettles discourses of truth, thus simultaneously intervening in debates about the epistemologies of the body and of theatre in context of the academy. Chapter 1: Methodological Anxieties Psychoanalytic theory provides a way in for investigating the dynamics of theatrical performance and its corporeal presence, by focusing on desire and its implication in the notions of loss and anxiety. The theories of the unconscious and the gaze have epistemological implications, shifting definitions of "presence" and "truth" in theatre performance and writing about theatre. This chapter tries to outline the rationale for, as well as to enact, an alternative methodology for writing, as an ethical response to loss that does not insist on consensus and truth. Chapter 2: (Refusing to) Look at Trauma This chapter examines the politics that strives to make suffering visible. Discursive binaries of public/private, dead/living, and invisible/visible underlie the politics of AIDS and sexuality. These discourses impact on the reception of Bill T. Jones's choreography, despite his use of modernist artistic processes in search of a bodily presence that aims to collapse the binary of representation (text) and its subject (being). The theory of the gaze shows this politics to be a phallocentric discourse; and narrative analysis traces the metanarrative that results in the commodification of oppositional identities, so that spectators participate in the politics as consumers. An ethical artistic response thus needs to shift its focus to the subjectivity of the spectator. Chapter 3: The Screen and the Viewer's Blindness By appealing to a transcendent reality, and by constituting spectators as a participative community, ritual theatre claims to enact change. The "truth" of ritual rests not on rational knowledge, but on the performer's competence to produce a shamanic presence, which director Brett Bailey embraces in his early work. Ritual presence operates by identification and belonging to a father/god as the source of meaning; but it represses the loss of this originary wholeness. Spectators of ritual theatre are drawn into an enactment of communion/community, the centre of which is, however, loss/emptiness. The claim of enacting change becomes problematic for its absence of truth. Bailey attempts to perform a hybrid, postcolonial aesthetics; but the problem rests in the larger context of performing the notion of "South Africa" , a communal identity hardened around the metanarrative of suffering, abjecting those that do not belong to the land of the father/god "“ foreigners that unsettle the meaning of South African identity. Conclusion: Bodies of Discontent The South African stage is circumscribed by political and economic discourses; the problematization of national identity is also a problematization of image-identification in the theatre. In search for a way to unsettle these interrogative discourses, two moments of performing foreignness are examined, one fictional, one theatrical. These moments enact a parallel to the feminine hysteric, who disturbs the phallocentric truth of the psychoanalyst through body performance. These moments of disturbing spectatorship are reflected in the works of performance artist Marina Abramovic. Her explorations into passive-aggression, shamanism and finally theatricality and the morality of spectatorship allow for an overview of the issues raised in this thesis regarding body, viewing, and subjecthood. Sensitivity to the body and its discontent on the part of the viewer becomes crucial to ethical performance.
Keywords: Abramovic, Marina; Performance art -- South Africa; Drama -- Psychological aspects; Psychic trauma Performance art -- Psychological aspects; Loss (Psychology); Ritual in art; Art, Modern -- 20th century